Correlation between weight-adjusted waist index and coronary heart disease: NHANES 1999–2020 - Liu, Yan; Sun, Shougang; Zou, Qi; Tao, Ting; Li, Dian; Han, Guodong; Wei, Zhiliang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe weight adjusted waist index (WWI) represents a novel indicator for assessing central obesity. The objective of this study is to investigate the association between WWI and coronary heart disease (CHD).MethodThe data of 44,528 participants in total were gathered from NHANES database from 1999 to 2020. WWI is calculated as the waist circumference (WC, cm) divided by the square root of the body weight (kg), and CHD was determined based on participants’ self-reports. The association between WWI and CHD was examined using multiple logistic regression analysis, restrictive cubic spline (RCS), receiver operating characteristic (ROC) curve, mediation analysis, subgroup and interaction analyses.ResultThis was a cross-sectional investigation. A total of 44,528 participants were included [50.23% male; mean WWI 10.89 (0.01) cm/√kg]. The multivariate logistic regression analysis revealed that in three models, one-standard-deviation increment in WWI was associated with an increased probability of CHD occurrence by 2.39 (2.22,2.57),1.47 (1.32,1.65), and 1.15 (1.00,1.32) times, respectively. Additionally, RCS analysis indicated a linear relationship between WWI and CHD. and the ROC analysis results showed that the discriminatory power of WWI for CHD was superior to that of body mass index (BMI) and WC. Glycated hemoglobin (HbA1c) partially mediated the relationship between WWI and CHD. Subgroup and interaction analyses confirmed that age, systolic blood pressure, and diabetes status had a significant impact on the association between WWI and CHD (P for interaction <0.05).ConclusionThe level of WWI has been demonstrated to be associated with an increased risk of CHD. Specifically, as WWI increases, the risk of CHD becomes higher. On this basis, it is hypothesized that WWI may potentially serve as an independent risk factor for CAD, thereby highlighting the substantial value of WWI in the identification and management of CHD.